2020
DOI: 10.2196/23382
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Electronic Health Record Usability as a Predictor of Task Load and Burnout Among US Physicians: Mediation Analysis

Abstract: Background Electronic health record (EHR) usability and physician task load both contribute to physician professional burnout. The association between perceived EHR usability and workload has not previously been studied at a national level. Better understanding these interactions could give further information as to the drivers of extraneous task load. Objective This study aimed to determine the relationship between physician-perceived EHR usability and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 57 publications
2
56
1
Order By: Relevance
“…These include, for example, the management of data privacy [ 1 ] or digital competences to enhance appropriate patient communication via internet [ 6 ]. In addition, new tasks make demands such as increasing time spent with documentation [ 7 , 8 ] or with low usability electronic health records [ 9 ] and technical support among colleagues [ 10 ], which were previously beyond the scope of work of health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…These include, for example, the management of data privacy [ 1 ] or digital competences to enhance appropriate patient communication via internet [ 6 ]. In addition, new tasks make demands such as increasing time spent with documentation [ 7 , 8 ] or with low usability electronic health records [ 9 ] and technical support among colleagues [ 10 ], which were previously beyond the scope of work of health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The Adler-Milstein paper et al paper [ 1 ] described above fell into this category. Another excellent paper by Melnick et al [ 6 ] performed a secondary analysis of a survey of US physicians from all specialties to determine the association between physicians’ perceived EHR usability and workload and their professional burnout. They found a strong relationship between EHR usability and workload, with more favorable usability associated with a lower task load.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive load is understood as the amount of mental load imposed on a person when solving a particular task and the associated required capacity of the human working memory [49]. In studies that also intend to evaluate electronic solutions as reported here and in the implementation of respective solutions in clinical practice, it is imperative to pay attention to this phenomenon, as cognitive load is related to the development of burnout and distress in EMRs [50]. However, in this study, after a certain period of use, the PCM was considered easier to use and became more familiar.…”
Section: Discussionmentioning
confidence: 99%